Seroprevalence and Associated Risk Factors of Coxiella burnetti in Small Ruminants in Southern States of Peninsular Malaysia - Ismael, Nur Aisyah; Fitri, Wan-Nor; Rahman, Nur Husna Abdul; Abidin, Zulkhairi Azizi Zainal; Jesse, Faez Firdaus Abdullah (Universitas Airlangga, 2025)
Q fever is caused by the bacteria Coxiella burnetii, a zoonotic disease that causes abortions and stillbirths in ruminants. The seroprevalence of Q fever in small ruminants, such as sheep and goats, can vary widely depending on geographical location, farming practices, and the prevalence of the disease in the area. The main objective of this study is to determine the prevalence of infectious reproductive diseases affecting the small ruminant population in the southern state of Peninsular Malaysia and its associated risk factors. The animals (n = 184), comprising 24 sheep and 160 goats, were from the states of Negeri Sembilan and Johor. Before sampling, a physical examination was conducted on the animal to establish its health status. An enzyme-linked immunosorbent assay was performed on the serum to detect the seroprevalence of infectious reproductive diseases in Q fever. Farm animal records and observations were designed to assess the risk factors associated with the prevalence of Q fever. The seroprevalence of Q fever in small ruminants was 2.7% (5/184). Male animals have a higher prevalence of Q fever at 3.63% (2/55) than female animals at 2.3% (3/129). Goats managed intensively were found to have a higher seroprevalence at 4.08% (2/49) than those managed semi-intensively at 2.17% (3/138). The state of origin factor was significantly associated with the seropositivity of Q fever. This study revealed the existence of low seroprevalence of Q fever among small ruminants in selected states and farms in Peninsular Malaysia. However, the low seroprevalence of Q fever suggests a persistent exposure to C. burnetti, which could present a public health threat and a substantial risk to the ruminant industry.